COMPARATIVE EFFECTIVENESS OF FIXED-DOSE COMBINATIONS OF LISINOPRIL/AMLODIPINE AND ENALAPRIL/HYDROCHLOROTHIAZIDE - S. V. Nedogoda; E. V. Chumachek; A. A. Ledyaeva; A. V. Tsoma; A. S. Salasyuk (Кардиоваскулярная терапия и профилактика, 2013)
Aim. To compare clinical effectiveness and tolerability of the fixed-dose combinations of lisinopril/amlodipine (Ekvator) and enalapril/hydrochlorothiazide (Co-renitec) in high and very-high risk patients with Stage I–II arterial hypertension, whose blood pressure (BP) levels were not normalised during the preceding antihypertensive monotherapy.Material and methods. This blind, randomised (envelope method), parallel study included 27 patients in each group. For 6 months, participants received the first medication (1 tablet a day, in the morning). After the 14-day wash-out phase, they were switched to another medication and received either Ekvator (lisinopril 10 mg plus amlodipine 5 mg) or Co-renitec (enalapril 20 mg plus hydrochlorothiazide 12,5 mg).Results. After 6 months of the treatment, more than 78% of the patients receiving Ekvator achieved target BP levels, in contrast to the participants receiving Co-renitec. Moreover, the treatment with Ekvator was associated with a significant reduction in the myocardial thickness of the posterior left ventricular wall and the carotid-femoral pulse wave velocity, as well as with a significant improvement in lipid metabolism parameters.Conclusion. Ekvator was more effective than Co-renitec in terms of antihypertensive activity, left ventricular hypertrophy reduction, and arterial elasticity improvement, as well as trough/peak ratio improvement.